2006
DOI: 10.1039/b514939h
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine particles at workplaces of a primary aluminium smelter

Abstract: The number concentration and size distribution of ultrafine particles in a Søderberg and a prebake potroom of an aluminium primary smelter have been measured using a scanning mobility particle spectrometer. The particle morphology was studied by transmission electron microscopy (TEM). The study shows the existence of elevated number concentrations of ultrafine particles in both potrooms. The main source of these particles is likely to be the process of anode changing. The ultrafine particles were measured dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 17 publications
5
30
0
2
Order By: Relevance
“…What does exist is focused either on particle morphology or particle aging in smelters (22,23). Although respirable particulate, inhalable particulate, and total particulate concentrations have been reported, these have focused on a few potroom jobs (14,16).…”
Section: Introductionmentioning
confidence: 99%
“…What does exist is focused either on particle morphology or particle aging in smelters (22,23). Although respirable particulate, inhalable particulate, and total particulate concentrations have been reported, these have focused on a few potroom jobs (14,16).…”
Section: Introductionmentioning
confidence: 99%
“…Asphalt workers are exposed to UFPs not only from traffi c but also from asphalt paving (Elihn et al, 2008 ). Exposure to UFPs at the workplace may also be high due to indoor sources, which are common in many industrial workplaces, for example, in metal foundries and smelters, and engine machining facilities Thomassen et al, 2006 ;Evans et al, 2008 ), where combustion or " hot " processes take place. UFPs are produced, for example, in welding, metal grinding, smelting, and brazing.…”
Section: Exposurementioning
confidence: 99%
“…UFPs are produced, for example, in welding, metal grinding, smelting, and brazing. Concentrations at workplaces can be higher than in any other microenvironment, even above 1,000,000 cm − 3 (Thomassen et al, 2006 ).…”
Section: Exposurementioning
confidence: 99%
“…The authors concluded that no carbon black is released in the reactor and pelletizing areas (as ultrafine or PM 10 ) from the closed production lines under normal operating conditions. Thomassen et al (2006) measured particle concentrations in an aluminium smelter. During anode change they found a strong number mode below 10 nm as well as a mode in the range 50-100 nm.…”
Section: Ultrafine Particlesmentioning
confidence: 99%